Semantic Differential as One of the Possibilities of Investigating Lower Secondary School Pupils’ Attitudes toward Chemistry - Kubiatko, Milan (Scientia in educatione, 2016)
First, the study provides an example of work with semantic differential and second, it focuses on research on attitudes toward chemistry on the basis of data obtained via semantic differential. Chemistry belongs among less favorite school subjects, both in the Czech Republic and abroad. Questionnaires with scaled items are the most often used research tools for the investigation of attitudes towards chemistry. Semantic differential is used relatively rarely. The aim of research was to find out lower secondary school pupils’ attitudes towards chemistry and investigate the influence of grade and gender on the attitudes toward chemistry with the use of semantic differential. The sample consisted of 71 lower secondary school pupils. The research tool comprised 20 adjectives on the seven point scale. The reliability of the research tool was determined by the use of Cronbach’s alpha coefficient, which indicated high reliability. The factor analysis divided adjectives into four dimensions. The neutral attitude toward chemistry was detected on the basis of mean score. T-test showed a statistically significant gender differences with boys achieving a higher score. Youngest pupils also achieved a higher score in comparison with the older ones, but the difference was not statistically significant.